Sifat Fisik Batako dengan Penambahan Limbah Styrofoam - Herol Herol; Dea Fauziah Larasati; Isria Miharti Maherni Putri; Alma Nastasya (DPPM Universitas Pelita Bangsa, 2022)
Increasing population growth and changes in people's consumption methods have resulted in a higher amount of waste. Styrofoam is one of the most common types of waste. Styrofoam is included in the category of inorganic waste that is dangerous both from health and the environment, it is necessary to process styrofoam waste, one of which is by making styrofoam as a building block material. Styrofoam which has a light weight is expected to make the weight of the bricks lighter. The purpose of this study was to determine the physical properties of the bricks with the addition of Styrofoam. The addition of styrofoam will replace sand with levels of 0%, 10%, 25%, and 50%. Visual observation of the bricks with the addition of styrofoam has white spots, gray color. The more styrofoam added, the harder it will be to get a perfect angle on the bricks. Testing the density and specific gravity of the bricks with the addition of styrofoam, it can be concluded that the higher the content of styrofoam as a substitute for sand, the smaller the density and specific gravity of the bricks because the unit weight of the styrofoam is very light. testing the water absorption of the bricks with the addition of styrofoam resulted in the absorption of water in the bricks will be smaller as more and more levels of styrofoam are added, that's due to the watertight nature of styrofoam. Brick Styrofoam content of 0%, 10%, 25%, and 50% included in the quality I according to SNI 03-0349-1989 which is smaller than 25%. Quality I is brick used for load bearing construction, usually used for unprotected construction (outside the roof). Keywords: Batako, Berat Jenis, Penyerapan Air, Styrofoam